Early‐life malnutrition causes gastrointestinal dysmotility that is sexually dimorphic. Issue 12 (6th July 2020) - Soni, Krishnakant G.; Dike, Peace N.; Suh, Ji Ho; Halder, Tripti; Edwards, Price T.; Foong, Jaime P. P.; Conner, Margaret E.; Preidis, Geoffrey A.
Abstract: Background: Slow gastrointestinal (GI) transit occurs in moderate‐to‐severe malnutrition. Mechanisms underlying malnutrition‐associated dysmotility remain unknown, partially due to lack of animal models. This study sought to characterize GI dysmotility in mouse models of malnutrition. Methods: Neonatal mice were malnourished by timed maternal separation. Alternatively, low‐protein, low‐fat diet was administered to dams, with malnourished neonates tested at two weeks or weaned to the same chow and tested as young adults. We determined total GI transit time by carmine red gavage, colonic motility by rectal bead latency, and both gastric emptying and small bowel motility with fluorescein isothiocyanate‐conjugated dextran. We assessed histology with light microscopy, ex vivo contractility and permeability with force‐transduction and Ussing chamber studies, and gut microbiota composition by 16S rDNA sequencing. Key Results: Both models of neonatal malnutrition and young adult malnourished males but not females exhibited moderate growth faltering, stunting, and grossly abnormal stomachs. Progression of fluorescent dye was impaired in both neonatal models of malnutrition, whereas gastric emptying was delayed only in maternally separated pups and malnourished young adult females. Malnourished young adult males but not females had atrophic GI mucosa, exaggerated intestinal contractile responses, and increased gut barrier permeability. These sex‐specific abnormalities were associated with altered gut microbial communities. Conclusions & Inferences: Multiple models of early‐life malnutrition exhibit delayed upper GI transit. Malnutrition affects young adult males more profoundly than females. These models will facilitate future studies to identify mechanisms underlying malnutrition‐induced pathophysiology and sex‐specific regulatory effects. Abstract : Multiple mouse models of early postnatal malnutrition exhibit slow small bowel progression of FITC‐dextran, delayed gastric emptying, and abnormal gross appearance of the stomach. Altered duodenal contractility and permeability are specific to malnourished males.